Caracterização genética dos hantavírus em roedores sigmodontíneos e humanos em área endêmica de síndrome cardiopulmonar por hantavírus no estado de Minas Gerais - Limongi, Jean Ezequiel (2013)
The hantaviruses are among the most important zoonotic pathogens of humans, especially due to high fatality, those associated with Hantavirus Pulmonary Syndrome (HPS). In Brazil, more than 1600 cases of HPS have been confirmed since 1993, with a fatality rate of 40%. The viral genotypes associated with HPS in humans, as well as those present in wild rodents were investigated in an endemic area of the state of Minas Gerais in this study. Furthermore, the seroprevalence for hantaviruses, the karyotyping of rodent species captured and the population dynamics of these animals on the Cerrado vegetation types were also evaluated in an ecoepidemiological approach. The ELISA and / or RT-PCR were used to test sera from human cases of SPH and wild rodents and rodent lung fragments. In our study, six patients were evaluated, of these six (100%) were seroreactive in ELISA in six (100%) was possible to amplify viral genetic material and in five (83.3%) was possible sequencing. Were observed in all the viral genotype Araraquara (ARAV), but with the formation of two well-defined clusters. The case fatality rate was 50%. Regarding rodents, 258 specimens were captured. Nine taxa were identified to species level and seven in genus level, all belonging to the subfamily Sigmodontinae. Necromys lasiurus was the most abundant (70.2). We observed a greater diversity of rodents in a fitofisionomy called semi-deciduous dry forest (07 taxa in species level and four in genus level). The winter dry season was associated with the highest capture success (p <0.0001). There was a higher prevalence of pregnancy during the rainy season (p <0.0001). There was a prevalence of IgG antibodies against hantavirus of 1.6%, all specimens of N. lasiurus. Among the four seroreactive rodents, three (75%) was possible to amplify viral genetic material and two (50%) was possible sequencing. Only ARAV viral genotype was observed. Samples of rodents had higher phylogenetic identity with the genotype sequenced of the human sample of Uberlândia, Minas Gerais, where the rodents were also captured. Samples identified with ARAV analyzed in this study were distributed at a distance of approximately 400 kilometers. Despite the geographical distance, we observed a high phylogenetic identity between two samples 384 km distant from each other. The environmental and demographic changes that have occurred in recent decades in the study area affected the ecology of wild rodents and facilitated the occurrence of hantavirus infections in humans and the emergence of HPS in this region, mainly ARAV transmitted by N. lasiurus. The observation in this study only the genotype ARAV in specimens of N. lasiurus and humans, does not exclude the possibility of co-circulation of other viral genotypes in this area, beyond the possibility of the existence of other reservoirs of hantaviruses, including non-rodents.